2010
DOI: 10.1016/j.ejcts.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Primary neuroendocrine tumours of the thymus: a clinicopathologic and prognostic study in 19 patients☆

Abstract: The prognosis of primary neuroendocrine tumours of the thymus is related to the grading of the neoplasm, the presence of a paraneoplastic syndrome and to the Masaoka staging but not to the postoperative radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…They have an estimated incidence of 3/10,000,000 people a year. [5,6] Approximately 250 patients with TCTs had been reported as of 2009, [7] and they account for approximately 2% of all carcinoid tumors that arise from various organs. [2] In addition, TCTs occur three times more frequently in males [1] and are most commonly seen in the fifth decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have an estimated incidence of 3/10,000,000 people a year. [5,6] Approximately 250 patients with TCTs had been reported as of 2009, [7] and they account for approximately 2% of all carcinoid tumors that arise from various organs. [2] In addition, TCTs occur three times more frequently in males [1] and are most commonly seen in the fifth decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is usually administered as the primary therapy for unresectable tumors or as an adjuvant to resection, [1] and many authors have reported that it can achieve good local control. [7,9] It also may help to ameliorate the symptoms of paraneoplastic syndromes. [1] There is no standard regimen for CHT, and a wide variety of agents have been employed.…”
Section: Discussionmentioning
confidence: 99%
“…In a neoadjuvant setting, Cardillo et al [68] reported 2 patients who had received dacarbazine, vincristine, and cyclophosphamide as induction therapy, which then rendered surgery possible, both having been excluded previously.…”
Section: Anti-proliferative Therapymentioning
confidence: 99%
“…Most SRS have been performed with 111 In-octreotide-SPECT, with little information on either 68 Ga-DOTA-TOC/DOTATATE PET/CT or 18 FDG PET/CT in thymic NENs. As a relatively aggressive tumour, several case reports have demonstrated 18 FDG uptake in thymic NENs, an uncommon finding in most other NENs [47][48][49] .…”
Section: Nuclear Medicinementioning
confidence: 99%
See 1 more Smart Citation